The Effect of Chitosan Addition on Phase Composition and Detection Sensitivity of Fe3O4/Chitosan Magnetic Label Nanoparticles Based on Giant Magnetoresistance Sensor - Prayoga, Galih Aji; Oktarisa, Yuvita; Antarnusa, Ganesha; Fitriani, Nur Shabrina; Aryani, Refi Meilia; Suherman, Andri; Guntara, Yudi (Journal of Energy, Material, and Instrumentation Technology, 2024)
This study describes how phase composition affects the ability of giant magnetoresistance (GMR) chip-based sensors to detect magnetic labels made of Fe3O4 and Fe3O4/chitosan that were synthesized using the co-precipitation method. X-ray diffraction (XRD) analysis revealed that the synthesized nanoparticles were a mixture of magnetite and maghemite phases. The most intense diffraction peak at 2θ = 35.6° (311) confirmed the presence of the magnetite phase. The addition of chitosan significantly increased the proportion of the maghemite phase from 10% to 25%, with the appearance of an additional peak at 2θ = 33° (221). The modification of Fe3O4 nanoparticles into Fe3O4/chitosan nanocomposites resulted in changes in sensor sensitivity. The GMR sensor successfully detected Fe3O4 and Fe3O4/chitosan magnetic labels within 30 seconds with high sensitivities of 0.746 and 0.761 mV/( g/mL), respectively. The limit of detection (LOD) was also very low at 0.419 and 0.428 g/mL. These findings show that Fe3O4/chitosan nanocomposites integrated GMR chip-based sensors can be a dependable instrument for detecting a variety of biomolecules such as Bovine serum albumin (BSA).